Analisis Kinerja Kondensor Direct Contact Tipe Jetspray Berdasarkan Efektivitas dan Efisiensi Thermal PT Geothermal Energy Ulubelu - Elli Prastyo (Jurnal Teknik: Media Pengembangan Ilmu dan Aplikasi Teknik, 2021)
PT Pertamina geothermal energy (PGE) Ulubelu uses jetspray-type condensers with the task of changing the vapour phase from turbine (steam tubin) to liquid. Condenser input fluid is the output of turbines (steam and non condensable gas), operating at a constant pressure of 0,08 bar and an average temperature of 28oC. Evaluation of condenser performance is based on the temperature and flow rate (condenser entry fluid and cooled water flow rate) against the value of thermal efficiency and effectiveness. The highest effectiveness value of 79,4% occurred when the Qaktual value was 10,891oC, while the lowest effectiveness value of 78,2% occurred when the Qaktual value was 10,306oC. The highest condenser thermal efficiency occurred in week 4 at 52,3% with Qair 441,149,944.2 kJ/h. Qair value of 417.424.072,6 kJ/h resulted in a condenser thermal efficiency of 49,5% in the first week. The calculation results were then visualized using a graph showing when Q was raised from 4,17.108 kJ/kg to 4,4.108 kJ/kg condenser efficiency increased by 0,6%.